Phytochemicals of Beluntas (Pluchea indica (L) Less.) and their health benefits - Putu Wira Kusuma Putra, I Made Jawi, Anak Agung Ngurah Subawa, Nyoman Mantik Astawa, Agung Wiwiek Indrayani, I Gede Widhiantara, Putu Angga Wiradana, Mochammad Aqilah Herdiansyah (Journal of Applied Pharmaceutical Science, 2025)
Bioactive compounds derived from plants are acquiring global popularity due to their safety and diverse applications as medicinal agents. Beluntas, also known as Pluchea indica, is a shrub abundantly found in coastal regions and is rich in several classes of phytochemicals that are highly significant in the biomedical field, particularly those based on natural products. The purpose of this review is to provide insights by highlighting research related to the bioactive compounds that can be obtained from P. indica. This review summarizes research data published in peer-reviewed manuscripts in English. Our search relied on scientific search engines and the following databases: Google Scholar, as well as scientific databases such as Scopus, PubMed, Crossref, and Web of Science, along with various publishers including Taylor and Francis, Elsevier, Wiley, Thieme, Bentham, Sage, SpringerLink, and Wiley– Blackwell. The traditional use of P. indica has been documented in several regions of Asia, including Indonesia, Thailand, Malaysia, and India. The phytochemicals of P. indica are thought to exhibit pharmacological effects such as antihyperlipidemic, antidiabetic, anticancer, antibacterial, anti-inflammatory, and antioxidant activities. Preclinical studies have demonstrated the pharmacological effects of P. indica extracts; however, limited data are available regarding the mechanism of action of this plant in clinical-scale studies. The phytochemicals of P. indica hold potential for development as herbal medicines or phytopharmaceuticals, creating possibilities for discovering new therapeutic agents and introducing compounds with previously known pharmacological effects.
Keywords: Pluchea indica, natural products, pharmacological, bioactivities, biomedical application